Why Are There So Few Female Top Executives in Egalitarian Welfare States? - Magnus Henrekson; Mikael Stenkula (Research Institute of Industrial Economics (IFN), 2009)
We identify pertinent institutions governing the structure of payoffs with regard to female career progression. Drawing on recent insights in behavioral economics, we hypothesize that interactions between psychological mechanisms and the institutional setup may be important determinants of cross-country differences in the level and evolution of female representation in executive positions in the business sector. We test this proposition informally by exploring whether it can be used to account for some of the observed differences between the Anglo-Saxon and Scandinavian countries in this respect. Three particularly important conclusions emerge: (i) broad welfare state policy promotes high female labor force participation, but blunts incentives to pursue top executive positions in the business sector; (ii) therefore, it is likely to be misleading to use the share of female executives as a proxy for gender equality in welfare states; and (iii) psychological mechanisms are likely to amplify the effects of policies and institutions.
Keywords: D13; D63; J16; J20; M52; 330; Career choice; Career incentives; Gender equality; Parental leave; Household production; Weibliche Führungskräfte; Erwerbsverlauf; Frauen; Gleichberechtigung; Haushaltsproduktion; Elternzeit; Verhaltensökonomik; Australien; Großbritannien; Kanada; USA; Nordeuropa